Exploring Digital Tools for Teaching Essay Writing Course in Higher Education: Padlet, Kahoot, YouTube, Essaybot, Grammarly - Arimuliani Ahmad; Mukhaiyar; Atmazaki, (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Enormous digital tools can assist teachers or students in the teaching and learning process in face-to-face meetings and virtual environments. During Pandemic Covid-19, government policy forced educators to decide and design online learning for all education levels from kindergarten, elementary, junior high school, senior high school, and university. Nevertheless, many free digital tools intended free access for educators that could be utilized as synchronous or asynchronous learning. This article explores utilizing five digital tools for online learning such as Padlet, Kahoot, YouTube, Essaybot, and Grammarly due to teaching Essay Writing course. It is descriptively explained how the researchers used a learning collaboration tool, a content creation tool, a content sharing tool to engage students’ interaction in the Essay Writing course. This article was considered sharing information and recommendation for other teachers to implement free digital tools to increase their learning process and achieve learning outcomes. The teachers and instructional designers may explore these digital tools, adopt relevant tools to their discipline, and do further research.